The Fatwas of Indonesian Ulema Council in The Era of Covid-19 Pandemic: An Islamic Legal Maxim Perspective - Bisri, Hasan; Anwar, Yayan Khaerul; Husni, Husni (Research and Development Institution, Darussalam Institute for Islamic Studies, 2022)
One of the triggers for the spread of the COVID-19 virus is a crowd of people, while several Muslim religious ritual activities are carried out in the form of a crowd (congregation). To avoid crowds of people, the Indonesian Ulema Council issued religious fatwas so those ritual activities would not become a cluster for the spread of COVID-19. This study analyzes the Indonesian Ulema Council’s (MUI) fatwas during the COVID-19 pandemic using the legal maxim perspective. This study uses the literature review method. Some primary and secondary literature on MUI fatwas are analyzed critically to obtain a complete, detailed, clear, and systematic picture of MUI fatwas. The study results show that the entire MUI fatwa is based on the Islamic legal maxim theoretical framework, which aims to keep Muslims away from harm, eliminate difficulties and difficulties, and endeavor to benefit as many people as possible. Besides, the entire Fatwa refers to authoritative Islamic sources, namely the Koran, the Prophet’s Hadith, scholars’ opinions, and experts' views. This study’s results can be applied as a guideline for Muslims and Muslim medical personnel in implementing Islamic teachings in the era of the COVID-19 pandemic.